To determine which equations are in the \( y = mx + b \) form, we need to identify equations where \( y \) is isolated on one side of the equation. This means rearranging the equations if necessary.
Let's analyze each equation:
-
\( y = 5x - 4 \)
- This is already in \( y = mx + b \) form.
-
\( y = -2x + 3 \)
- This is already in \( y = mx + b \) form.
-
\( y = 3x + 1 \)
- This is already in \( y = mx + b \) form.
-
\( 2y = 6x + 2 \)
- Divide both sides by 2: \[ y = 3x + 1 \]
- This is now in \( y = mx + b \) form.
-
\( y - 5x = 2 \)
- Rearranging gives: \[ y = 5x + 2 \]
- This is now in \( y = mx + b \) form.
-
\( y - 4x + 1 = 0 \)
- Rearranging gives: \[ y = 4x - 1 \]
- This is now in \( y = mx + b \) form.
In summary, all of the equations can be expressed in \( y = mx + b \) form:
- Yes
- Yes
- Yes
- Yes
- Yes
- Yes